Exercise therapy in primary biliary cirrhosis: the importance of moving while sitting on a surgical waiting list—a case study. Issue 3 (12th April 2016) - Hallsworth, Kate; Jopson, Laura; Jones, David E; Trenell, Michael I
Abstract : Background: It is being increasingly recognised that reduced cardiorespiratory fitness is associated with poorer outcomes after major surgery. Exercise limitation and reduced aerobic capacity are common in people with end-stage liver disease. There is limited evidence about the role of exercise therapy in the management of primary biliary cirrhosis (PBC) and no studies have looked at the effect of exercise in people with PBC who are awaiting liver transplantation. This case study is the first to report that personalised exercise therapy improves cardiorespiratory fitness in a patient with PBC without worsening symptoms of severe fatigue. Methods: Cardiopulmonary exercise testing was used to assess cardiorespiratory fitness in a patient with end-stage PBC prior to listing for transplantation. A personalised exercise programme was designed to improve cardiorespiratory fitness while the patient was on the transplant waiting list. Results: Anaerobic threshold, VO2PEAK and maximum workload all improved with regular exercise. Fatigue levels remained unaltered. Conclusions: This patient tolerated and adhered to a personalised exercise programme for a prolonged period of time while awaiting surgery despite significant fatigue and disease burden. Liver transplantation was successfully completed and this woman remains well over 2 years post-surgery.